Forest-based composites for higher indoor air quality.
At the crossroads of indoor air quality and environmental concerns lies OSIRYS, a concept of forest-based composites for facades and interior partitions. Composed of biopolymers and natural fibres, the new material promises to reduce emissions of pollutants and actively eliminate other contaminants.